The Influence Of Teacher Personality Competencies On Character Values Of Students - Gultom, Tamara Yulina; Siregar, Nurliani; Nainggolan, Justinus Ray (Jurnal Pendidikan, Sains Sosial, dan Agama, 2021)
This research aim know influence competence the personality of Christian Religious Education (PAK) teachers towards mark character participant students at SMA Negeri 1 Pantai Cermin. The research used method descriptive quantitative with technique data collection through questionnaire Likert scale that has been tested validity and reliability. Data analysis was carried out with simple linear regression test use SPSS.Results study show that competence The personality of the PAK teacher has an influence positive and significant to mark character participant educate, shown with mark significance of 0.010 (<0.05). Coefficient correlation (R) of 0.503 indicates connection Enough strong, whereas mark determination (R Square) 0.581 means competence teacher personality contributes 58.1% to mark character students. In conclusion, competence PAK teacher's personality plays a role important in formation character participant educate so that need Keep going improved through development self and support environment school and family.